Follow-up of Methanol-related Visual Defects in a Cohort Study: Initial Severity Predicts Long-term Outcome - Farzad Gheshlaghi; Anselm Wong; Rezvan Firuzfar; Keyvan Jenab; Shayan Gheshlaghi; Golnoosh Shahverdi; Nastaran Eizadi-Mood (Wolters Kluwer Medknow Publications, 2024)
Objective: Methanol poisoning can occur either intentionally through the consumption of methanol-containing products or accidentally through ingestion, resulting in visual impairment. We assessed the long-term visual sequelae in patients with methanol poisoning. Methods: This prospective cohort study was conducted at referral centers, Khorshid and Alzahra University Hospitals, affiliated with Isfahan University of Medical Sciences, Isfahan, Iran. The study included patients hospitalized for methanol poisoning from June 22, 2018, to June 21, 2020, with follow-up extended until June 2021. Toxico-clinical and ophthalmologic examination data were collected from patients upon hospital admission, discharge, and during follow-up. Findings: Thirty-nine patients were assessed in this study. The majority of them (94.9%) were male, with an average age of 34 years. Patients who presented with reduced visual acuity (VA) upon admission subsequently showed abnormalities (in acuity and visual fields) during follow-up (n = 13). Among the patients who displayed visual field defects on admission, bilateral optic disc atrophy was observed in follow-up (n = 13). Conversely, patients who reported blurred vision, with or without photophobia upon admission, had normal results in their follow-up eye examinations. Among the 36 patients who underwent dialysis, 14 (38.9%) exhibited visual impairment during follow-up examinations. Additionally, 38 patients received sodium bicarbonate, and 14 of them (36.85%) also presented ocular abnormalities. Conclusion: Patients who demonstrated VA deficits upon admission are more likely to experience long-term VA and visual field defects, as well as optic disc atrophy. Patients who solely complained of blurred vision, with or without photophobia, during admission were less likely to develop long-term visual defects.